Current Ratio, Debt to Equity Ratio, Return on Equity, Dividend Payout Ratio dan Size terhadap Return Saham Perusahaan Trade, Service & Investment Indonesia - Annisa Nauli Sinaga; Eric Eric; Rudy Rudy; Valencia Wiltan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
Large companies (Size) have more stable sales and established assets so that the ability to get greater profits. This is one of the attractions for investors thereby increasing stock returns. This study aims to analyze and test whether Current Ratio (CR), DER, ROE, Dividend Payout Ratio & Size affect the stock returns on trade, service & investment companies listed on the Stock Exchange for the 2016-2018 period. This research is a deductive, quantitative and descriptive approach. The total population of trade, service & investment companies listed on the Stock Exchange is 144 companies. The technique of determining the sample using consideration samples so that the samples obtained by 36 companies. Analysis of the data to be tested multiple linear regression and test the classical assumptions. The results of the study individually Current Ratio (CR), Return on Equity (ROE), Dividend Payout Ratio and Size have a positive effect on stock returns while DER has no effect on stock returns. Together, Current Ratio, DER, ROE, Dividend Payout Ratio and Size have a significant effect on stock returns on trade, service & investment companies listed on the Stock Exchange in the 2016-2018 period. Keywords : Current Ratio, Debt to Equity Ratio, Return on Equity, Dividend Payout Ratio, Size and Stock Return